Prognostic significance of L-type amino acid transporter 1 (LAT1) expression in cutaneous melanoma. Issue 5 (October 2015) - Shimizu, Akira; Kaira, Kyoichi; Kato, Madoka; Yasuda, Masahito; Takahashi, Ayumi; Tominaga, Hideyuki; Oriuchi, Noboru; Nagamori, Shushi; Kanai, Yoshikatsu; Oyama, Tetsunari; Asao, Takayuki; Ishikawa, Osamu
<x xml:space="preserve">Abstract</x> Amino acid transporters play a crucial role in the development and invasiveness of cancer cells. However, it remains unclear whether or not the expression of L-type amino acid transporter 1 (LAT1) has prognostic significance in patients with cutaneous melanoma. A total of 128 patients with cutaneous melanoma were evaluated. Tumor sections were stained by immunohistochemistry for LAT1, CD98, Ki-67, and microvessel density determined by CD34 and p53. We also analyzed 30 specimens of patients with melanocytic nevi as negative controls. LAT1 and CD98 were highly expressed in 58% (75/128) and 75% (97/128), respectively. The rates of positivity for LAT1 in the melanocytic nevi were 0% (0/30). The expression of LAT1 was associated significantly with tumor thickness, T factor, CD98 expression, cell proliferation (Ki-67), and microvessel density (CD34). By Spearman's rank test, LAT1 expression was correlated with CD98, Ki-67, and CD34. By univariate analysis, tumor thickness, ulceration, disease staging, LAT1, and CD34 showed a significant relationship with overall survival and disease-free survival. Furthermore, a multivariate analysis confirmed that LAT1 was an independent prognostic factor for predicting a poor prognosis. This study had a small sample size. LAT1 can serve as a significant prognostic factor to predict a poor outcome and it may therefore play an important role in the aggressiveness of cutaneous melanoma.